Nurses' Experiences in Safe Handling of Chemotherapeutic Agents: The Taiwan Case. Issue 5 (September 2016) - Chen, Hai-chiao; Lu, Zxy-yann Jane; Lee, Shu-Hui
Abstract : Background: Nurses are the least compliant with the guidelines for use of personal protective equipment (PPE) among health professionals. While the literature regarding nurses not following the guidelines focuses on nonuse of PPE, the experiences of using PPE from nurses' perspectives have not been examined. Objective: The aim of this study was to explore the concerns of nurses regarding their decision to use or not to use PPE in the cultural context of Taiwan. Methods: An ethnographic design was used, and ethnographic interviews of 57 nurses working with chemotherapy for more than 2 years were conducted. The participating nurses were observed in 2 accredited medical centers with oncology care teams in Taiwan. The constant comparison method was applied for data analysis, and cultural themes were generated from all transcripts. Results: Wearing PPE was identified as an obstacle to professional image and performance. Nurses transformed safety into efficiency and prioritized social roles over professional roles. Experienced nurses, as insiders, believed that they have gained clinical wisdom to avoid occupational exposure to chemotherapy toxicity. Conclusions: This study explored the characteristics of clinical wisdom regarding PPE use in the context of Taiwanese chemotherapy care. Perceived professional image, efficiency on the job, PPE cost, and hospital rules influenced the use or nonuse of PPE by oncology care nurses. Implications for Practice: Acceptable nurse-patient ratios and refraining from chemotherapy toxicity exposure for pregnant and breast-feeding women are advocated for policy making. The experiential expertise of nurses should be shared as credible evidence in developing guidelines.